The saturation of interband Faraday rotation in Bi2Se3. (18th April 2017) - Hakl, M.; Ohnoutek, L.; Veis, M.; Drašar, Č.; Materna, A.; Strzelecka, G.; Hruban, A.; Slobodeniuk, A.; Piot, B. A.; Martinez, G.; Potemski, M.; Orlita, M.
Abstract: Bismuth selenide – the prominent topological insulator – has been recently reported as a material exhibiting an extraordinary strong Faraday rotation. This effect has been identified as due to interband excitations in bulk promoting electrons from the valence to the conduction band, in which the electron gas is partially spin-polarized due to the Zeeman effect. In this work, we test the Faraday rotation in Bi2 Se3 in high magnetic fields, when the conduction band electrons reach their full spin polarization. We find that the Faraday angle becomes in this regime almost independent of the applied magnetic field. This contrasts with the Faraday effect observed in this system at low magnetic fields, where the Faraday angle scales linearly with B and may thus be described by a conventional Verdet law.